EFEKTIFITAS FATWA MAJELIS ULAMA INDONESIA SUMATERA UTARA NOMOR 03/Kep/MUI-SU/IV/2011 TENTANG HUKUM PREWEDDING PHOTO (STUDI KASUS DI KELURAHAN SIDOREJO HILIR KECAMATAN MEDAN TEMBUNG) - Ritonga, Zulkipli (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
Prewedding Photo is defined as a photo activity between the two brides-to-be before the marriage bond. It is known that the prospective bride and groom who have not pledged their marriage with a marriage contract are prohibited from touching. Whereas the purpose of marriage is to avoid lust. But what is happening now, the implementation of Prewedding Photo is increasingly widespread in the community. The Indonesian Ulema Council of North Sumatra has issued a fatwa Number: 03/Kep/MUI-SU/IV/2011 regarding the prohibition of Prewedding Photo which states that a Prewedding Photo which contains a photo of the bride and groom posing holding hands, hugging before the marriage ceremony is carried out is therefore haram. If a photo is needed or desired as an indication of the identity of who is getting married, then it should display photos of the bride and groom politely in a separate way, cover the aurat and do not violate Islamic law. That way, the desire to still display photos of the bride and groom can be fulfilled but does not violate the Shari'a. Researchers writing this thesis aims to determine the effectiveness of the fatwa of the Indonesian Ulema Council of North Sumatra regarding the Prewedding Photo Law in Sidorejo Hilil Village, Medan Tembung District, along with the views of the people in Sidorejo Hilir Village about the practice of Prewedding Photo. As a result, it was found that the people of Sidorejo Hilir Village did not know of the North Sumatran Indonesian Ulema Council fatwa regarding the Prewedding Photo Law, there were people who thought it was legal to do a Prewedding Photo because later they would get married too, however, there are still brides and grooms who do Prewedding Photo according to religious law, especially because it is Islamic teachings that say it is forbidden to come into contact with non-mahrams, not because of the fatwa. Most of the pre-wedding photos are done with poses that are forbidden in the North Sumatra MUI fatwa. The researcher concludes that it is time for the people of Sidorejo Hilir Village to receive information about the fatwas issued by the North Sumatran MUI and apply them in their daily life, one of which is by not practicing Prewedding Photos that violate religious law.